Abraham Ibn Ezra's "Secrets" in the Early and Later Torah Commentaries - Kreisel, Howard (Jewish Thought, 2020)
In this article, I compare Ibn Ezra's treatment of two esoteric doctrines in his early commentary to Genesis and Exodus, written in Lucca, and his later commentary on these books, written in Rouen. The first doctrine is the nature of the biblical angels, and the second is the rational soul and its ultimate end. The article opens with a brief account of Ibn Ezra's composition of the commentary on the Torah and the approach he adopts, and moves on to describe the changes in his approach in his later commentary on the books of Genesis and Exodus. It then presents an outline of the topics on which Ibn Ezra alludes to secret doctrines and the philosophical background of some of his secrets, before turning to a detailed analysis of the two topics under consideration. I argue that while Ibn Ezra expands upon some of these secrets in his later commentaries, only readers adept in the sciences and philosophy can truly appreciate them. This is even more true regarding the readers of his earlier commentaries. Yet Ibn Ezra elaborated on some of the secrets in his later commentaries not because the Jewish intellectual elite of Northern France were more familiar with the scientific and philosophical background of the secrets than the Italian Jewish intellectual elite, enabling them to better appreciate his exposition. Rather, he did so because he wished to prod his readers in the Christian world to study the sciences and philosophy, and he saw that the succinct hints he had provided in his first commentary were not sufficient to accomplish this goal.